Infliximab Plus Intravenous Immunoglobulin (IVIG) Versus IVIG Alone as Initial Therapy in Children With Kawasaki Disease Presenting With Coronary Artery Lesions: Is Dual Therapy More Effective?. Issue 10 (October 2018) - Jone, Pei-Ni; Anderson, Marsha S.; Mulvahill, Matthew J.; Heizer, Heather; Glodé, Mary P.; Dominguez, Samuel R.
Abstract : Background: We previously demonstrated that 80% of Kawasaki disease (KD) patients who develop coronary artery lesions (CALs) have them at diagnosis. We postulated that KD patients presenting with CALs represent a group that may benefit from more aggressive initial therapy. Infliximab has been shown to decrease inflammation in KD patients when added to standard therapy. We compared outcomes of KD patients with CALs initially treated with intravenous immunoglobulin (IVIG) alone versus IVIG plus infliximab. Methods: Medical records of KD patients from January 2009 to July 2016 were retrospectively reviewed. CALs were defined as a left anterior descending or right coronary artery Z score ≥2.5. KD patients with CALs on initial echocardiogram treated with IVIG alone were compared with those treated with IVIG plus infliximab. Clinical characteristics were compared between groups using Wilcoxon rank-sum test, χ 2 test and Fischer's exact tests; length of stay was analyzed using log-normal regression and need for additional therapy using logistic regression. Effect of treatment on CALs between groups was assessed using linear mixed models. Results: Sixty-nine KD patients with CALs at presentation were included. Fifteen of 34 (44%) patients treated with IVIG alone required additional therapy compared with 4 of 35 (11%) patients treated with IVIG plus infliximab ( P = 0.003). There were no significant differences between treatment groups for length of stay, CALs or C-reactive protein fall. Conclusions: IVIG plus infliximab as initial therapy reduces the need for additional therapy in KD patients presenting with CALs. Intensified initial therapy, consisting of infliximab plus IVIG, could be considered for this group of KD patients.